José Coelho de Noronha: artes e ofício nas Minas Gerais do século XVIII - Aziz José de Oliveira Pedrosa (2012)
Once it is known the relevance of the artistic production related to the gilt on the seven hundred, this dissertation brings up the life and the work of the master sculptor José Coelho de Noronha in Minas Gerais in the 18th century. However, the research had as its major boost the absence of accurate studies concerning Noronha's performance, which appears to be contradictory, due to the fame and the prestige gained by him at the time of his performance. Therefore, a new glance is taken at the subject owing to the survey of relevant documentary records that have been unknown by Minas Gerais art historiography for years and that today give some important help to understand part of this master sculptor's route. In that sense, it is registered that Noronha worked as a sculptor in the Main Church of Nossa Senhora do Pilar in São João Del Rey town and also in the works of carving done at Mariana Sé, besides other churches around Minas Gerais where he has done hard labour. Then, what we have is the analysis of an art that is marked by influence relationships of the seventeenth century art, of the Lisbon Joanino style and of baroque final aspect: the rococo style, besides the influence of other sources of repertory assimilation. It is also cited the possible partnership relationship kept by Noronha with other sculptors that worked in Minas Gerais who, somehow, were guides to the routes tracked by the eighteenth century art, in European style, in Minas Gerais.